Drones and the future of armed conflict - Cortright, David 1946-; Fairhurst, Rachel; Wall, Kristen (University of Chicago Press, 2015)
Presenting a robust conversation among leading scholars in the areas of international legal standards, counterterrorism strategy, humanitarian law, and the ethics of force, Drones and the Future of Armed Conflict takes account of current American drone campaigns and the developing legal, ethical, and strategic implications of this new way of warfare. Among the contributions to this volume are a thorough examination of the American government's legal justifications for the targeting of enemies using drones, an analysis of American drone campaigns' notable successes and failures, and a discussion of the linked issues of human rights, freedom of information, and government accountability.